A Study of Callus Imperfecta in Callotasis - Inoue, Akio; Shirahama, Masahiro; Kakizoe, Mituo; Sato, Naoto (Orthopedics & Traumatology, 1995)
Callotasis is now widely used in the orthopaedic fiedl to treat leg-length discrepancy and short stature. However complications often occur with this technique. We used callotasis with an Orthofix fixator to treat fourty-nine bone segments in twenty-six patients. The complication of callus imperfecta occurred in eleven bone segments (ten patients). We investigated the cause of this complication, and how to prevent and treat it. Causes were influenced by age, method of osteotomy, and speed and quantity of distraction. Bone marrow transplantation, electrical stimulation and accordion operation were effective countermeasures useful for treating this complication.